METABOLIC AND CIRCULATING microRNA PROFILING DURING MATERNAL DIABETES AND DIFFERENCES BY DIABETES TYPE - Pheiffer, Carmen; Masete, Matladi; Dias, Stephanie; Malaza, Nompumelelo; Adam, Sumaiya (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES In pregnancies complicated by maternal diabetes, metabolic and epigenetic effects such as dysregulated microRNA (miRNA) expression, may influence pregnancy outcomes. This study aimed to assess the effect of maternal diabetes type on metabolic and circulating miRNA expression. METHODOLOGY C-peptide, total and high molecular weight (HMW) adiponectin, C-reactive protein (CRP) and triglyceride concentrations were quantified in serum (16 to 27 weeks gestation) from women with pregestational type 1 diabetes (T1D, n = 7), type 2 diabetes (T2D, n = 14), new T2D (n = 12), gestational diabetes mellitus (GDM, n = 17) and normoglycaemia (n = 24) using enzyme-linked immunosorbent assays (ELISA). MiRNAs were profiled in a subset of samples using the human serum/plasma miScript miRNA PCR array (n = 4 per group). RESULTS Lower C-peptide total and HMW adiponectin levels with higher CRP levels were observed in women with T2D and GDM compared to women with T1D and normoglycaemia. The expression of miR-19b-3p was lower in women with GDM (9.8-fold, p=0.033); miR-20a-5p was lower in women with T1D (4.5-fold, p=0.047) and miR-29a-3p was higher in women with T2D (1.8-fold, p=0.002). Several other miRNAs were differentially expressed between the diabetes groups but were not statistically significant. Bioinformatic analysis identified messenger RNA targets common and unique to the differentially expressed miRNAs. CONCLUSION Metabolic parameters and miRNA levels differed according to the type of maternal diabetes. MiRNA expression differences between T1D, T2D and GDM could be related to intrauterine hyperglycemia and epigenetic programming. These findings may be interesting areas for further studies.